Evaluating human life using court decisions on damages for pain and suffering - Andrea Leiter; Magdalena Thöni; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper provides a framework to evaluate human life based on civil court decisions on damages for pain and suffering. Using judgements from Germany and Austria over the last 25 years, we calculate an average Value of Damages for Pain and Suffering (VDPS) of about EUR 1.79 millions, with a minimum (maximum) of around EUR 0.67 (4.62) millions. Our approach also allows to calculate the value of body parts and body functions, which might be of interest if information on the benefit of an individual's change in life quality is not (entirely) available.
Keywords: I10; J17; K13; 330; Pain and suffering; Value of Statistical Life (VSL); Quality Adjusted Life Years (QALY); tort law